KINERJA BADAN PENANGGULANGAN BENCANA DAERAH KOTA DENPASAR DALAM MITIGASI BENCANA KEBAKARAN - Sriastuti, Komang Ary Tribuana; Supriliyani, Ni Wayan; Prabawati, Ni Putu Anik (CITIZEN CHARTER, 2023)
The Performance of the Denpasar City Regional Disaster Management Agency in Fire Disaster Mitigation Denpasar City Regional Disaster Management Agency (BPBD) in Fire Disaster Mitigation is guided by Law Number 24 of 2007 concerning Disaster Management and Regulation of the Minister of Home Affairs Number 33 of 2006 concerning Guidelines for Disaster Mitigation. However, there are performance problems in its implementation, so it is necessary to measure the performance of public organizations to review how the Denpasar City BPBD is performing in fire disaster mitigation. This research uses a type of qualitative research with a descriptive approach. The data sources used are primary and secondary data. The informant determination technique in this study used purposive sampling. This research is measured by the theory of performance measurement of public organizations according to Agus Dwiyanto (2006:50). The results showed that the performance of the Denpasar City BPBD in fire disaster mitigation was quite good, namely on the productivity indicator, the performance of the Denpasar City BPBD in fire disaster mitigation had not run optimally because there was a need to optimize the number of human resources and budget. On service quality indicators, the performance of BPBD Denpasar City in mitigating fire disasters has been going well. On the responsiveness indicator, the performance of the Denpasar City BPBD is not optimal because it needs to optimize the outreach/education program and training/education program. On the responsibility indicator, the performance of the Denpasar City BPBD in fire disaster mitigation has been running optimally. Then on the accountability indicator, the performance of the Denpasar CityBPBD in mitigating fire disasters has been running optimally.